THE INFLUENCE OF GENDER AND FAMILY BACKGROUND ON FINANCIAL BEHAVIOR WITH FINANCIAL LITERACY AS A MEDIATION VARIABLE: STUDY ON GENERATION Z TEENS IN JAYAPURA CITY - Palti Manalu; Isma Shalihi Ahlia; Sheilla Putri Agustin (Literacy: Jurnal Pendidikan Ekonomi, 2024)
This study examines the determinants of financial behavior among Generation Z in Jayapura Papua with a specific focus on gender and family background influences mediated by financial literacy Using path analysis the research surveyed 223 respondents aged 17 25 years through accidental sampling The findings reveal that financial literacy directly influences Generation Z s financial behavior with a significance value of 0 003 p lt; 0 05 Both gender and family background significantly affect financial literacy contributing 13 1 to its variance The study demonstrates that gender indirectly influences financial behavior through financial literacy with indirect effects 0 01312 exceeding direct effects 0 153 However family background shows stronger direct effects 0 425 compared to indirect effects 0 0276 on financial behavior indicating that financial literacy does not effectively mediate this relationship The overall model explains 24 7 of the variance in financial behavior These findings contribute to understanding the complex relationships between demographic factors financial literacy and financial behavior among Generation Z in eastern Indonesia s context The study recommends future research to incorporate additional variables to enhance the model s explanatory power and employ more precise measurement techniques < p>